Pattern of weight loss of young female and male wrestlers - Viveiros, L.; Moreira, A.; Zourdos, M. C.; Aoki, M. S.; Capitani, C. D. (The Journal of Strength and Conditioning Research, 2015)
The aim of this study was to investigate the magnitude of rapid weight loss (RWL) of female and male young wrestlers at the Brazilian high-school games. High-school wrestlers (females: n = 16, 13 ± 2 years; males: n = 15, 13 ± 2 years) participated in this study. The official weigh-in was conducted 24 hours before competition. Immediately after the official weigh-in, wrestlers completed a hydration habits and a standardized weight loss questionnaires. Twenty-four hours later, wrestlers took part in an unofficial prematch weigh-in. Sodium, potassium, chloride, hematocrit, and hemoglobin were measured immediately before the first competitive match by iSTAT Blood Gas Analyzer. A significant body mass increase was observed from the official weigh-in to the prematch weigh-in (females: 2.7 ± 1.4 kg and males: 1.5 ± 0.9 kg; p = 0.05) with significantly greater body mass increase in females (6.3%) vs. males (3.1%) (p = 0.05). Rapid weight loss practices were exercised by 42.0% of the wrestlers. Furthermore, 46.2% of those who performed RWL practices reported side effects, which they perceived negatively altered past performance. Despite RWL and subsequent body mass increase, all biomarkers (sodium, potassium, chloride, hematocrit, and hemoglobin) were in the normal range at the prematch weigh-in. The majority (82.0%) of the athletes agreed that hydration habits are important to health and performance. It seems that although wrestlers acknowledge negative performance effects due to RWL, the practice is still exercised among both female and male wrestlers. Therefore, educational programs should be implemented in high-school athletes to discourage RWL and provide information for exercise and nutritional strategies to maintain a healthy body mass and avoid chronic health issues.